Simplified Procedure for Drawing of Artwork of Prototype PCB - Bhadane, Pravin; Lal, Aparna (International Journal of Computer Sciences and Engineering, 2018)
Work on simplifying the drawing of Artwork required for making of prototype PCB has been carried out and reported in the present article. The students of electronics find PCB Artwork making procedure tedious and time consuming. To overcome this problem, we have presented here the simplified as well as motivating procedure. Work started with a selection of circuit diagram that contains various types of components and connectors. After that the rough layout is planned with consideration of dimensions of components. Various steps in drawing of Artwork like placement of footprint of components, making netlist as per the circuit diagram, manual routing, etc. are discussed with example. Utilisation of various facilities provided by computer aided PCB layout making softwares are also discussed in the present work. Procedure of making of postscript file and its printout using postscript editor like corel draw is also discussed. Present work is helpful to the hobbyist and students of electronics for making of their project work.